Emotions in digital context: Finnish way of saying Pick me; we could make a good couple! - Holappa, Anne (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2012)
The world has become thoroughly mediated. Dating ads are cultural representations for negotiations of shared cultural models and evident personal meanings given to hetero-relationship. There is shared knowledge about how to act in online dating sites. This has an influence on the ways average Finnish people describe the idea of desirable relationship in online dating ads. The study contained 943 Finnish heterosexual online dating ads collected in 2012. The site was chosen because dating ads here were semi-structured. Besides the structured form there was also an open space for free expression which could be utilized for making the impression. The data was analyzed using theoretically informed close readings; thematic analysis, intertextual reading and reflexive reading. The main results of how Finnish people represent the desirable grounds for relationship in online dating ads could be categorized under three main themes: first, the quotations from other media situations (intertextual source); second, the expressions referring to Finnish ethnicity and values; and third, the religious reference. Representation was mostly textual. The analysis revealed lack of digital possibilities in presentations of oneself or relationship in online environment.